Analisis Penerapan 3r (Reduce, Reuse, Recycle) Pada Masyarakat Di Sepanjang Aliran Siring Kelurahan Pondok Besi Kota Bengkulu - Morin Fadilah Putri; Singkam, Abdul Rahman (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2022)
The society around Pondok Besi sewage was believed to have contributed for mass of waste in Tapak Paderi beach, Bengkulu City. The bad habit of those people that usually dump their waste into the sewage, and disembogue to Tapak Paderi beach, needs to be resolved. Besides interfering the allure of Tapak Paderi beach, the plastic part of this waste will unravel into micro- and nanoplastic in the ocean. This research aims to analyze the application of 3R (reduce, reuse, recycle) on the society around Pondok Besi sewage. Data collection was conducted by interviewing using a designed questionnaire. The research discovered that application of 3R in the people around Pondok Besi sewage is very low. 55% of the respondents didn’t bring their reusable bag for shopping, 88% will still buy their wanted product though it results a massive waste. 75% of them also didn’t reuse their empty bottles/containers and neither recycle their inorganic waste, and none of the respondents recycle their organic waste. Moreover, 85% of the respondents can’t provide an example of activity as application of 3R. Based on these results, a further action to improve the awareness of people around Pondok Besi sewage in applying 3R is required.